Colorimetric detection of mercury ions using MnO2 nanorods as enzyme mimics. Issue 11 (7th June 2015) - Yang, Haiguan; Xiong, Yuhao; Zhang, Peng; Su, Linjing; Ye, Fanggui
<x xml:space="preserve">Abstract</x> In this study, a simple and novel "off–on" colorimetric sensor for the detection of mercury ions (Hg2+) in aqueous solution was developed.